Rail Geometry Analysis (From the Point of View of Wearing in the Operation) - Gerlici, Juraj; Lack, Tomas (Communications - Scientific letters of the University of Zilina, 2003)
Rail geometry analysis is, from the point of view of wearing in the operation, the question of present railway vehicles operation practice. The sequels of negative influence are reflected on the environment state. For the influence rate assessment various methods are used. The wearing state of rail road track is possible to assess in different manners. One of them is the assessment of geometric contact of railway wheel and rail profile. The significant information on the rail track operation state are Delta R function, Tangens Gamma function, effective conicity equivalent conicity, rail profile in the track wear analysis on the ground of real and theoretic rail profile geometry position difference. The fundament for another rail state assessment is the single wheel/rail profiles position assessment and common displaying in the railroad track. The poor real track quality state is the reason for necessary track maintenance and rail geometry quality improvement.